MENTAL HEALTH AND ENJOYMENT BY ARTICULATION: कलाभिव्यक्ति द्वारा मानसिक स्वास्थ्य एवं आनन्द प्राप्ति - Awasthi, Bindu (International Journal of Research -GRANTHAALAYAH, 2019)
Synonyms of Kala Anand- The symbolic mystery of mental health exists only in the etymology of the word Kala. According to Indian opinion, art is derived from the word kal-dhatu which means beautiful, soft, pleasant, words, ringing, counting, etc. in Sanskrit language. The word Kala is also made of hard metal, which means to mourn and to please. Apart from this, ’Kan’- meaning Anand (Kan Anandam) Lati Eti Kala. Thus in Sanskrit literature, references to the word Kala are found in about twenty meanings. कला आनन्द की पर्याय- कला शब्द की व्युत्पत्ति में ही मानसिक स्वास्थ्य का सांकेतिक रहस्य विद्यमान है। भारतीय मतानुसार कला शब्द-कल् धातु से व्युत्पन्न है जिसका अर्थ संस्कृत भाषा में सुन्दर, कोमल, सुखद्, शब्द करना, बजना, गिनना इत्यादि है। कला शब्द कड् धातु से भी बना है जिसका तात्पर्य है मदमस्त करना तथा प्रसन्न करना इत्यादि। इसके अतिरिक्त ‘कं’- अर्थात् आनन्द (कं आनन्दं) लाति इति कला। इस प्रकार संस्कृत साहित्य में लगभग बीस अर्थों में कला शब्द के संदर्भ मिलते हैं।